Assessing the effects of microencapsulated Lactobacillus salivarius and cowpea seed supplementation on broiler chicken growth and health status - Lefter, Nicoleta Aurelia; Gheorghe, Anca; Habeanu, Mihaela; Ciurescu, Georgeta; Dumitru, Mihaela; Untea, Arabela Elena; Vlaicu, Petru Alexandru (Frontiers in Veterinary Science, 2023)
This study aimed to assess the nutritional quality of cowpea seeds (cv. Doljana – CSD) and the impact of partially replacing soybean meal with CSD, along with the supplementation of microencapsulated Lactobacillus salivarius (LS), on the growth performance, selected carcass traits, biochemical plasma profile, tibia bone quality, and microbial populations in the ceca and excreta of broiler chickens aged 1 to 35 days. A total of 432 mixed-sex Ross 308 broiler chickens, aged one day, were randomly allocated to four groups, with 108 birds in each group, further divided into 6 pens containing 18 birds each. The experimental design featured a 2 × 2 factorial arrangement, with two cowpea seed levels (CSD0 and CSD15%) and the presence or absence (Yes/No) of microencapsulated LS probiotic (0 and 1 g/kg feed). The experimental diets did not significantly influenced (p > 0.05) production performances. However, the production efficiency factor was notably higher in the CSD0 (336.8%) and CSD15 (332.2%) groups with LS compared to CSD0 (322.4%) and CSD15 (320.6%) groups without LS supplementation. Regarding carcass traits, the CSD15 group with LS supplementation exhibited higher dressing (70.69%) and liver (2.47%) percentages compared to the other groups. Plasma profile analysis revealed significant reductions (p < 0.05) in total cholesterol (from 115 mg/dL to 105 mg/dL) and triglycerides (from 54.80 mg/dL to 46.80 mg/dL) in the CSD15 group with LS supplementation compared to the CSD0 group, with or without LS supplementation. Moreover, the CSD15 group with LS had significantly higher total protein, albumin, and calcium levels and significantly lower (p < 0.05) uric acid levels compared to the CSD0 group, irrespective of LS supplementation. Tibia bone traits and minerals showed no significant effects. However, the pH exhibited a linear decrease from 6.90 in the CSD0 group without LS to 6.69 in the CSD15 group with LS supplementation. In terms of cecal microbial populations, Coliforms decreased from 7.14 CFU/g in the CSD15 group without LS to 5.48 CFU/g in the CSD15 group with LS. Significant alterations were also observed in Clostridium spp., E. coli, Enterococcus spp., and Staphylococcus spp. in the ceca and excreta of the CSD15 group with LS supplementation compared to the CSD0 group, with or without LS supplementation. Beneficial bacteria, specifically Lactobacillus spp., significantly increased in the cecal content of CSD0 (9.06 CFU/g) and CSD15 (9.01 CFU/g) groups with LS compared to CSD0 (8.41 CFU/g) and CSD15 (8.11 CFU/g) groups without LS. In summary, this study suggests that cowpea seeds can be used as a partial replacement for soybean meal in broiler chicken diets, and microencapsulated Lactobacillus salivarius can be employed as a probiotic supplement.